2016
DOI: 10.1007/s00134-016-4414-4
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blockers in septic shock to optimize hemodynamics? Yes

Abstract: Septic shock represents one of the maximum physical stresses to the organism. The physiological response to stress includes increased release of catecholamines, leading to a stimulation of cardiac β1-adrenergic receptors thereby increasing heart rate and ventricular contractility in order to increase global and microvascular blood flow and oxygen delivery to vital organs. Yet there are adverse effects of adrenergic stimulation including tachyarrhythmias, increased cardiac oxygen consumption with risk of cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…27 Sepsis, trauma (especially traumatic brain injury), burns, post-cardiac arrest syndrome, subarachnoid haemorrhage, pheochromocytoma or immoderate beta-2 stimulation are all classic examples of such states and each one of them has already been ascribed an adrenergic storm epitome such as the more specific Takotsubo cardiomyopathy (TCM) or the all-inclusive term stress-cardiomyopathy (SCM). 28,29 TCM is not a mere epiphenomenon but portends a poor risk by itself as shown by Templin et al 30 Within this context, beta-blockade has been advocated in several scenarios: CA resuscitation, 31 traumatic brain injury, 32,33 sepsis 34 and burns. 35 Decatecholaminisation is an 'umbrella' term, 36 encircling much more than beta-blockers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Sepsis, trauma (especially traumatic brain injury), burns, post-cardiac arrest syndrome, subarachnoid haemorrhage, pheochromocytoma or immoderate beta-2 stimulation are all classic examples of such states and each one of them has already been ascribed an adrenergic storm epitome such as the more specific Takotsubo cardiomyopathy (TCM) or the all-inclusive term stress-cardiomyopathy (SCM). 28,29 TCM is not a mere epiphenomenon but portends a poor risk by itself as shown by Templin et al 30 Within this context, beta-blockade has been advocated in several scenarios: CA resuscitation, 31 traumatic brain injury, 32,33 sepsis 34 and burns. 35 Decatecholaminisation is an 'umbrella' term, 36 encircling much more than beta-blockers.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 TCM is not a mere epiphenomenon but portends a poor risk by itself as shown by Templin et al. 30 Within this context, beta-blockade has been advocated in several scenarios: CA resuscitation, 31 traumatic brain injury, 32,33 sepsis 34 and burns. 35…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials on sepsis-related cardiomyopathy under β-blockade are limited. Nevertheless, a few studies have reported improvements in heart rate, cardia function, and mortality rate during septic shock [19]. Morelli et al, 2013, conducted a randomized controlled trial on patients with severe septic shock, where 77 of them were randomly assigned to receive a continuous infusion of the short-acting β-blocker esmolol titrated to maintain a heart rate between 80 and 94/min.…”
Section: Introductionmentioning
confidence: 99%
“…Un cúmulo de acontecimientos neuroendocrinos y humorales ocurrirán con la finalidad de mantener el «equilibrio» entre el huésped y el agente infeccioso, es esta respuesta exagerada la causa de la disfunción orgánica aguda que pone en peligro la vida y alcanza una mortalidad hospitalaria de 18 a 35%. 1,2 Diversos estudios a través de los años se han encargado de estudiar y establecer el impacto pronóstico de las alteraciones a nivel de la microcirculación en este grupo de pacientes. 3,4 Existen diferentes métodos disponibles para detectar hipoperfusión tisular y alteración microvascular en el paciente críticamente enfermo que van desde la clínica (hipotensión, piel moteada, acrocianosis, llenado capilar lento o disminución de la temperatura) hasta otros más sofisticados como la tonometría gástrica, capnometría sublingual o espectroscopia.…”
Section: Introductionunclassified